Biologie van die wingerdfilloksera Phylloxera vitifoliae (Fitch)(Homoptera: Phylloxeridae) in Suid-Afrika - De Klerk, C. A. (Christiaan Andreas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScConsEcol)--Stellenbosch University, 1970.